Moving a step further from "integrative CALL". What's to come?. Issue 6 (17th August 2016) - Gimeno-Sanz, Ana
Abstract: This paper reflects upon the evolution of technology-enhanced language learning throughout the past two decades based on the author's own experience and how Information and Communications Technologies have played a prominent role on how language teaching pedagogies have evolved alongside the technologies themselves. Reference is made to the milestones that have marked the evolution of computer-assisted language learning (CALL) and how future trends are developing. The author discusses her vision of CALL and develops the concept of "atomised CALL", a theory first introduced in 2013. Atomised CALL describes the field of CALL from 2010 onwards, i.e. from Mark Warschauer's definition of "integrative CALL". In relation to Bax's theory about the "normalisation" of CALL, the author defends that, as long as technology continues to evolve and new gadgets appear on the market, there will always be a place for CALL developers and authors to find the optimum way of pedagogically exploiting these forever-emerging technological developments.